Seeking Begumpura : the social vision of anticaste intellectuals - Omvedt, Gail (Navayana Pub. : Distributed by IPD Alternatives, 2008)
Study of the socioeconomic perspectives of the eminent anticaste intellectuals; some articles analyze Bhakti movement and Hindu nationalism over a period of five centuries.